The Role of PJKR Lecturers in Strengthening Character Education - Suastika Nurafiati; Herman Herman (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
Character education is the most important thing in developing students' potential to become human beings with character. One of the supporting elements in the development of character education in national education is the teaching staff. Lecturers as educators participate in the development of educational character. The role of lecturers in carrying out the tri dharma mandate of higher education is carried out through education and teaching, research and development, community service. The objective of this study is related to the role of PJKR doses in strengthening student character education at STKIP YPUP Makassar. The research was conducted using qualitative research methods where data was obtained using interview, observation and documentation techniques. The results of the study show that the role of PJKR lecturers in strengthening character education is carried out in education, teaching and student development. Lecturers integrate values into learning starting from the formulation of teaching plans, implementation of learning and teaching methods. Student advisors, lecturers become role models that can be emulated by students in socializing and behaving.